2009
DOI: 10.37285/ijpsn.2009.2.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Superdisintegrants and their Concentrations on the Dissolution of Topiramate Immediate Release Tablets

Abstract: The purpose of this study was to investigate the efficiency of superdisintegrants: sodium starch glycolate, croscarmellose sodium and crospovidone in promoting tablet disintegration and drug dissolution of Topiramate immediate release tablets. The efficiency of superdisintegrants was tested, by considering four concentrations, viz., like 2%, 3%, 4% and 5% in the formulations. The dissolution was carried out in USP apparatus II at 50 rpm with distilled water as a dissolution medium. The dissolution rate of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Croscarmellose (along with other disintegrants) was studied for its effect with different concentrations on the dissolution of topiramate tablets. Priya found that the dissolution rate of topiramate tablets increased each time when the concentration of croscarmellose is increased from 2% to 3%, 4%, and 5% [22].…”
Section: Results and Discussion I)mentioning
confidence: 99%
“…Croscarmellose (along with other disintegrants) was studied for its effect with different concentrations on the dissolution of topiramate tablets. Priya found that the dissolution rate of topiramate tablets increased each time when the concentration of croscarmellose is increased from 2% to 3%, 4%, and 5% [22].…”
Section: Results and Discussion I)mentioning
confidence: 99%
“…The apparatus was operated until all residual matter was completely eliminated following the vertical movement of the basket assembly within the beaker. The duration required for all six tablets to completely pass through the 10-mesh screen was referred to as the disintegration time (Priya et al, 2009).…”
Section: Disintegration Timementioning
confidence: 99%